2021
DOI: 10.1111/tpj.15609
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in ZmSAUR15 contribute to the formation of immature embryo‐derived embryonic calluses in maize

Abstract: The ability of immature maize (Zea mays) embryos to form embryonic calluses (ECs) is highly genotype dependent, which limits transgenic breeding development in maize. Here, we report the association mapbased cloning of ZmSAUR15 using an association panel (AP) consisting of 309 inbred lines with diverse formation abilities for ECs. We demonstrated that ZmSAUR15, which encodes a small auxin-upregulated RNA, acts as a negative effector in maize EC induction. Polymorphisms in the ZmSAUR15 promoter that influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Much progress has been made in the elucidation of the underlying mechanisms of SE ( Fehér, 2015 ; Horstman et al, 2017 ; Su et al, 2021 ). However, EC induction and plant regeneration are affected by many factors, including genotypes, explants, hormones, and concentrations of various substances in the induction medium ( Guo et al, 2020 ; Wang et al, 2020 , 2022 ). So far, the acquisition of EC has been shown as the critical process in plant SE ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Much progress has been made in the elucidation of the underlying mechanisms of SE ( Fehér, 2015 ; Horstman et al, 2017 ; Su et al, 2021 ). However, EC induction and plant regeneration are affected by many factors, including genotypes, explants, hormones, and concentrations of various substances in the induction medium ( Guo et al, 2020 ; Wang et al, 2020 , 2022 ). So far, the acquisition of EC has been shown as the critical process in plant SE ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, EC induction and plant regeneration are affected by many factors, including genotypes, explants, hormones, and concentrations of various substances in the induction medium ( Guo et al, 2020 ; Wang et al, 2020 , 2022 ). So far, the acquisition of EC has been shown as the critical process in plant SE ( Wang et al, 2022 ). However, it is difficult to identify the cells capable of embryogenesis with morphological data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional genetic modification methods have a long cycle and are limited by natural variations [ 1 ], whereas transgenic breeding is able to break through these restrictions. In maize genetic transformation, the induction efficiency of embryogenic callus (EC) directly affects the transformation ratio of immature embryos [ 2 ]. Previous studies reported that EC induction from maize immature embryos was influenced by multiple factors, including genotypes, hormones, and compositions of induction media [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%